2002
DOI: 10.1128/aem.68.5.2605-2609.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Escherichia coli O157:H7 in Manure-Amended Soil

Abstract: Escherichia coli O157:H7 cells survived for up to 77, >226, and 231 days in manure-amended autoclaved soil held at 5, 15, and 21°C, respectively. Pathogen populations declined more rapidly in manure-amended unautoclaved soil under the same conditions, likely due to antagonistic interactions with indigenous soil microorganisms. E. coli O157:H7 cells were inactivated more rapidly in both autoclaved and unautoclaved soils amended with manure at a ratio of 1 part manure to 10 parts soil at 15 and 21°C than in soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
247
8
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(277 citation statements)
references
References 14 publications
20
247
8
2
Order By: Relevance
“…The latter was shown to occur for E. coli O157 in the environmental protozoan Acanthamoeba polyphaga (Barker et al, 1999). In contrast, the cumulative effect of the total indigenous microflora on E. coli survival is often negative as a result of predation, substrate competition and antagonism (Jiang et al, 2002;Unc et al, 2006;Semenov et al, 2007). Contrary to the declining populations that are often seen in natural habitats, populations of E. coli can increase in such substrates under sterile conditions, that is, without predatory, antagonistic or competing organisms.…”
Section: Presence and Diversity Of An Indigenous Microfloramentioning
confidence: 80%
See 2 more Smart Citations
“…The latter was shown to occur for E. coli O157 in the environmental protozoan Acanthamoeba polyphaga (Barker et al, 1999). In contrast, the cumulative effect of the total indigenous microflora on E. coli survival is often negative as a result of predation, substrate competition and antagonism (Jiang et al, 2002;Unc et al, 2006;Semenov et al, 2007). Contrary to the declining populations that are often seen in natural habitats, populations of E. coli can increase in such substrates under sterile conditions, that is, without predatory, antagonistic or competing organisms.…”
Section: Presence and Diversity Of An Indigenous Microfloramentioning
confidence: 80%
“…On the other hand, the fate of E. coli populations under complex natural conditions is often not accurately predictable . Although the conditions for survival of E. coli in soil, manure and water are considered to be less favourable than in the intestinal system (Tauxe et al, 1997), the organism has been observed to survive for days (at physiological (430 1C) temperature, aerobic and under nutrient-limiting conditions) to almost a year in the former habitats (Kudva et al, 1998;Fukushima et al, 1999;Jiang et al, 2002).…”
Section: Factors Affecting E Coli Fate In Open Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon may be due, at least partly, to potential changes in soil microbial composition including the native soil antibiotic-resistant bacteria (ARB) after the application of chemical fertilizer (Forsberg et al, 2014). Although chemical fertilizer had some effects on soil ARGs, these effects, not surprisingly, are weaker when compared with sewage sludge or chicken manure, considering that manure is rich in ARGs and ARBs , Jiang et al, 2002Ghosh and LaPara, 2007) and most ARGs are discharged from the municipal wastewater treatment process in the form of sewage sludge (Munir et al, 2011). However, land application of animal manure or sewage sludge does not universally increase ARGs in soils (Zhou et al, 2010) and this increase is not maintained long-term (Fahrenfeld et al, 2014).…”
Section: Responses Of Args Abundance and Compositionmentioning
confidence: 99%
“…The majority of storage systems are opentopped, so they collect precipitation but allow free gaseous exchange. Poor maintenance and earthen storages can lead to groundwater pollution (Rowsell et al, 1985; Table 2 Persistence of potentially pathogenic organisms in manure (based on Wang et al, 1996;Jiang et al, 2002;Bach et al, 2005a) Organism Persistence under experimental conditions (days) Barrington et al, 1991). Earthen storage, in areas with shallow bedrock, pervious soils, and shallow water tables endanger water supplies unless artificial liners are used (Barrington et al, 1991).…”
Section: Article In Pressmentioning
confidence: 99%